An alkynyl-protected Ag13−xCu6+x nanocluster for catalytic hydrogenation. Issue 1 (1st December 2022) - Gao, Yan-Li; Sun, Xueli; Tang, Xiongkai; Xie, Zhenlang; Tian, Guolong; Nan, Zi-Ang; Yang, Huayan; Shen, Hui
Abstract : A novel alkynyl-stabilized silver–copper alloy nanocluster of [Ag13− x Cu6+ x ( t BuC6 H4 CC)14 (PPh3 )6 ](SbF6 )3 has been prepared. The cluster exhibits high catalytic performance in catalytic hydrogenation reactions. Abstract : A novel alkynyl-stabilized silver–copper alloy nanocluster with the composition of [Ag13− x Cu6+ x ( t BuC6 H4 CC)14 (PPh3 )6 ](SbF6 )3 was prepared by the (PPh3 )2 CuBH4 -mediated reduction approach. The nanocluster features a centred disordered-octahedral Ag7 Cu6 kernel, which is protected by hybrid alkynyl and triphenylphosphine ligands. Structural comparison of this two-electron nanocluster with other alkynyl-capped Ag/Cu ones suggested that the structure of alkynyl ligands played an important role in dictating the structures of the resulting nanoclusters. The title cluster showed high performance in the catalytic hydrogenation of 4-nitrophenol, indicative of the bright future of cluster-based catalysts.